Ceftobiprole versus ceftriaxone ± linezolid in Community-Acquired Bacterial Pneumonia (CABP): Re-analysis of a randomized, phase 3 study using 2020 FDA guidance - Andrew F. Shorr; Mark E. Jones; Silke Friedmann; Daniel Ionescu; Mikael Saulay; Jennifer I. Smart; Marc Engelhardt (PLoS ONE, 2025)
Background Ceftobiprole is an advanced-generation cephalosporin with activity against methicillin-resistant Staphylococcus aureus, resistant pneumococci, and Enterobacterales. In a Phase 3 study in community-acquired bacterial pneumonia (CABP) performed prior to the current US Food and Drug Administration (FDA) guidance, clinical cure at the test-of-cure visit (TOC) was the primary endpoint. We present a re-analysis using early clinical success as the primary endpoint per the 2020 FDA CABP Guidance. Methods In this multicenter, double-blind study, patients with CABP requiring hospitalization were randomized to intravenous ceftobiprole (500 mg q8h) or ceftriaxone (2000 mg q24h) ± linezolid (600 mg q12h) for 3–14 days. The primary endpoint was clinical success at Day 3 (improvement in ≥2 symptoms of chest pain, cough, productive sputum, difficulty breathing). A 12.5% non-inferiority margin was used. Results Of the original 638 patients, 618 (97%) had ≥ 2 symptoms and were included in the Day 3 Intent-to-Treat (ITT) population for the re-analysis. The Day 3 modified ITT population consisted of 187 patients (29%) meeting additional FDA Guidance including Patient Outcomes Research Team (PORT) classification ≥III. Ceftobiprole was non-inferior to ceftriaxone for clinical success for Day 3 ITT (71.0% vs 71.1%) and Day 3 modified ITT (71.1% vs 66.7%) populations. The 28-day all-cause mortality was 1.6% (ceftobiprole) vs 2.6% (ceftriaxone) in the Day 3 ITT population and 2.1% vs 7.8% in the Day 3 modified ITT population. Conclusion Ceftobiprole was non-inferior to ceftriaxone ± linezolid for clinical success at Day 3 according to the current 2020 FDA CABP Guidance.